Malignant cysts of the male breast. Issue 745 (November 1987) - Stebbings, W. S.; George, B. D.; Boyle, S.; Plowman, P. N.; Gilmore, O. J.
Abstract : Two cases of male breast carcinoma presenting as cystic swellings are reported. Cysts of the male breast are rare, but unlike cysts in female breasts are more likely to represent significant pathology. We recommend consideration of excision biopsy of isolated cysts in male breasts.